cos^2(pi/6)=3/4
sin^2(pi/3)=3/4
cos^2x+3/4=cos^2(2x)+3/4
cos^2x=cos^2(2x) ; (cos2x=2cos^2x-1)
cos^2(2x)-cos^2x=0
(2cos^2x-1)^2-cos^2x=0
4cos^4x-4cos^2x+1-cos^2x=0; введу cos^2x=t
4t^2-5t+1=0
D=25-19=9
t1=(5+3)/8=1; cos^2x=1; cosx=+-1; x1=pik
t2=(5-3)/8=1/4; cos^2x=1/4;cosx=+-1/2; x2=+-pi/3+2pik ; x3=+-2pi/3+2pik
ответ x={pik;+-pi/3+2pik;+-2pi/3+2pik}
cos^2(pi/6)=3/4
sin^2(pi/3)=3/4
cos^2x+3/4=cos^2(2x)+3/4
cos^2x=cos^2(2x) ; (cos2x=2cos^2x-1)
cos^2(2x)-cos^2x=0
(2cos^2x-1)^2-cos^2x=0
4cos^4x-4cos^2x+1-cos^2x=0; введу cos^2x=t
4t^2-5t+1=0
D=25-19=9
t1=(5+3)/8=1; cos^2x=1; cosx=+-1; x1=pik
t2=(5-3)/8=1/4; cos^2x=1/4;cosx=+-1/2; x2=+-pi/3+2pik ; x3=+-2pi/3+2pik
ответ x={pik;+-pi/3+2pik;+-2pi/3+2pik}